Breve introducción a la terapia Gestalica de grupo - Safan, Desy (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The dichotomy between behavior therapy and humanistic therapy and the mutual lack of appreciation for the value of the schools of thought which underlie them has impeded progress in both areas. The purpose of this paper is to discuss a form of existential therapy, gestalt therapy. This trend is identified with Fritz Perls, Viennese, ex-disciple of Sigmund Freud. Perls succeeded in developing a body of theory and practice which were influenced not only by European phenomenology and existentialism but also by psychoanalysis as modified by W. Reich and the Form School. It has been considered among the existential therapies since it shares with these the attitude of involvement on the part of the therapist and the non-medical concept of cure.